Penerapan Moderasi Beragama di Masyarakat Desa Lingga Kecamatan Simpang Empat - Salsabilla, Adinda; Br Pohan, Juwita Dewi; Sinulingga, Nabila Oktarina; Nasution, Riska Syahputri; Fona, Tari Rizkya; Khalida, Wahyuni; Br Ginting, Elvira Dewi (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Lingga Village is one of the villages located in Simpang Empat District, Karo Regency with a Karo ethnic community. This ethnicity consists of various adherents of monotheistic religions such as Islam, Catholicism, Protestantism, and Pentecostalism. Religion plays an important role in social life to regulate human life and direct it to goodness in the world. This research aims to obtain an understanding and description of religious moderation and religious harmony in Lingga Village. The research methods used in this research are field observation research methods, interviews, and case studies. The results of the research show that religious moderation in Lingga Village is not too low. Some local people know the concept and dynamics of religious moderation and if we look at inter-religious harmony, the people of Lingga Village really uphold harmony where mutual respect and respect for differences. Keywords: Religious Moderation, Community, Harmony, Lingga Village.